The Ledra Palace Hotel and the ‘difficult history’ of modern Cyprus - Stylianou-Lambert, Theopisti; Heraclidou, Antigone (My University, 2022)
his paper explores the extent to which the recent turbulent history of Cyprus is reflected in an emblematic building, the Ledra Palace Hotel. The hotel is situated on Nicosia’s buffer zone, the Green Line that, since 1964, has divided the island into Greek Cypriot and Turkish sectors. Since its establishment in 1949 the Ledra Palace has been the background of the country’s key historical events. In this paper, the Ledra Palace is analysed as an integral part of Cyprus’ cultural heritage which contributes to the understanding and negotiation of the island’s difficult past.
Keywords: heritage; Ledra Palace; Cyprus; colonialism